Medial Translation as a Form of Interaction Between Print and Electronic Literature: The Example of Iain Pears’ Arcadia - Erik György ([sic])
The relationship between electronic and print literature is seldom researched, even though electronic literature has been around for several decades. This article focuses on one form of such relationship, namely medial translation. Drawing on the concepts from intermedial, adaptation and translation studies, the article develops the definition of medial translation and introduces its various forms, followed by examples of electronic or print literary works that illustrate the described processes. Since medial translations from electronic to print literature are rare, the article emphasizes the analysis of medial translation through Iain Pears’ Arcadia (2015), which first appeared as an iPad application and was later released in print.Keywords: medial translation, intermediality, electronic literature, print literature, ArcadiaIn Literature in the Digital Age (2016), Adam Hammond declares our present times a transitional period in literary culture between the print and the digital ages, marked by the emergence of such new literary forms as hypertext fiction, e-poetry, or virtual and augmented reality fiction. N. Katherine Hayles, one of the first scholars to provide an overarching definition of what is known today as electronic literature (e-literature), called these forms ‘digital born,’ “first-generation digital object[s] created on a computer and (usually) meant to be read on a computer” (3). Later, Bell et al. elaborated on this notion by stating that e-literature is “fiction written for and read on a computer screen that pursues its verbal, discursive, and/or conceptual complexity through the digital medium, and would lose something of its aesthetic and semiotic function if it were removed from that medium” (4). Digital media thus propose new opportunities for the literary-minded. For instance, they allow the incorporation of sound and animation as essential components of literary works, new variations of multi-path narratives that are hard to recreate in print, or a higher degree and new forms of interactivity, wherein readers often become characters in the story and can affect it in meaningful ways, to name only a few.